Type 2 Diabetes Mellitus and Early-Onset Colorectal Cancer: Mechanisms and Herbal Prevention Potential - Wibisono Hasanul Muhtaram; Mira Nupila Rahma; Ashila Sallama Nur Fadlila; Indri Tiffani; Lalu Abdul Mubarak; Retno Dwi Utami; Baiq Mayada Isqie; Florentcia Davina Gunawan; Made Prajnana Adhi Parasikan Susana; Nensy Dwi Astika; Pande Komang Inten Widya Iswara Oka; Kurniati Kurniati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Colorectal cancer is the third most commonly diagnosed cancer and the second leading cause of cancer-related mortality worldwide. The incidence of early-onset colorectal cancer has continued to increase, and type 2 diabetes mellitus (T2DM), particularly chronic hyperglycemia, has been proposed as one of its contributing risk factors. This study aimed to evaluate the potential of herbal compounds as complementary approaches targeting molecular pathways linking T2DM and colorectal cancer. A systematic literature review was conducted following the PRISMA guidelines using PubMed and ScienceDirect. Original articles published between 2021 and 2026, written in English, available in full text, and investigating single herbal compounds or plant extracts in colorectal cancer models were included. The reviewed studies demonstrated that several herbal compounds, including glycyrrhizin, freeze-dried jaboticaba peel, Osmanthus fragrans extract, Ganoderma lucidum polysaccharide, Corallocarpus glomeruliflorus extract, galangin, dictamnine, silymarin, Portulaca oleracea extract, and curcumin, modulated key molecular pathways involved in colorectal carcinogenesis, particularly NF-κB, MAPK, Wnt/β-catenin, and YAP/TAZ signaling. Although these preclinical findings suggest potential complementary roles for herbal bioactive compounds in colorectal cancer prevention, further translational studies and well-designed clinical trials are required to confirm their efficacy and safety in individuals with T2DM.